2018
DOI: 10.1186/s40425-018-0359-1
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression and prognostic value of PD-L1 in Extrapulmonary small cell carcinoma: a single institution experience

Abstract: BackgroundExtrapulmonary small cell carcinomas (ESCC) are rare but aggressive tumors. Relapses are common despite treatment with chemotherapy and/or radiotherapy. Prospective data for treatment of ESCC are lacking; treatment of these cancers usually incorporates lung small cell carcinoma treatment recommendations. Cancer staging remains the most important prognostic factor. Cancer immunotherapy targeting the PD-1/PD-L1 pathway has shown efficacy in multiple tumor types, and could be an appealing treatment stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
(24 reference statements)
1
15
1
Order By: Relevance
“…It has been proposed that gene expression could be potentially affected by genetic polymorphisms [21,61,62,63]. Alterations in the expression of PD-1 and PDL-1 were detected in many cancer types including gastric cancer, lung cancer, thyroid cancer, laryngeal carcinoma, extrapulmonary small cell carcinoma, and breast cancer [63,64,65,66,67,68,69].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that gene expression could be potentially affected by genetic polymorphisms [21,61,62,63]. Alterations in the expression of PD-1 and PDL-1 were detected in many cancer types including gastric cancer, lung cancer, thyroid cancer, laryngeal carcinoma, extrapulmonary small cell carcinoma, and breast cancer [63,64,65,66,67,68,69].…”
Section: Discussionmentioning
confidence: 99%
“…From our single institution review on PD-L1 expression of extrapulmonary small cell carcinomas (ESCC) between 1999 and 2016, we identified 2 cases of prostate origin, one of which had a positive PD-L1 combined score. Positive combined scores were detected in 12 of 34 (35%) total ESCC cases, with the majority arising from the genitourinary tract [14]. While our patient had a negative score, this review demonstrated that these rare tumors may still express PD-L1, and thus investigating PD-1 inhibitors could result in favorable outcomes among this population.…”
Section: Discussionmentioning
confidence: 61%
“…Patients with limited-stage disease with positive PD-L1 staining had a median 53 months overall survival compared to PD-L1 negative patients with limited-stage disease whose median overall survival was 15 months. Extensive stage patients had median overall survival that was similar between PD-L1 positive and negative groups, four months vs five months respectively, which was not statistically significant [26].…”
Section: Role Of Pd-l1mentioning
confidence: 70%